Pengusaha Transpor : Studi Tentang Pola-Pola Hubungan Hukum Antara Pengirim dengan PT. Bhanda Ghara Reksa - Permana, Bulova Deagustuta Bias; , Dr. Kelik Wardiono S.H.,MH (2017)
Today almost everyone uses their means of transportation for traveling. basically the use of means of transportation is one type of transportation activities. In a large dictionary Indonesian transport means to lift or carry or transmit. The function of transporting is to move freight or passengers from one place to another with the intent to increase the usability and value. Transportation is not only meant only for the carriage to humans, but also the goods, because in today's human needs is increasing, so the necessary means of transportation that can support the mobility of goods in order to arrive at a destination. In shipping goods not everyone can do it independently, as some people have different condition and limitation, such as the limitations of distance, time, or cost, a problem for some people. which became the object of research is how the patterns of the legal relationship between the sender and PT. Bhanda Ghara Reksa, and how the responsibility of PT. Bhanda Ghara Reksa if the delivery is not running smoothly. This research method is done with the normative doctrinal approach is descriptive analytical. The data used in primary and secondary data consisting of primary legal materials and secondary law. Library collection through literature. Data was collected by literature study and interviews. Data processing is done by means of an inventory of data and analytically identified doctrinal.